Emerging Disease-Modifying Therapies in Neurodegeneration With Brain Iron Accumulation (NBIA) Disorders - Iankova, Vassilena; Karin, Ivan; Klopstock, Thomas; Schneider, Susanne A. (Frontiers in Neurology, 2021)
Neurodegeneration with Brain Iron Accumulation (NBIA) is a heterogeneous group of progressive neurodegenerative diseases characterized by iron deposition in the globus pallidus and the substantia nigra. As of today, 15 distinct monogenetic disease entities have been identified. The four most common forms are pantothenate kinase-associated neurodegeneration (PKAN), phospholipase A2 group VI (PLA2G6)-associated neurodegeneration (PLAN), beta-propeller protein-associated neurodegeneration (BPAN) and mitochondrial membrane protein-associated neurodegeneration (MPAN). NBIA disorders present with a wide spectrum of clinical symptoms such as movement disorder signs (dystonia, parkinsonism, chorea), pyramidal involvement (e.g. spasticity), speech disorders, cognitive decline, psychomotor retardation, and ocular abnormalities. Treatment remains largely symptomatic but new drugs are in the pipeline. In this review, we discuss the rationale of new compounds, summarize results from clinical trials, provide an overview of important results in cell lines and animal models and discuss the future development of disease-modifying therapies for NBIA disorders. A general mechanistic approach for treatment of NBIA disorders is with iron chelators which bind and remove iron. Few studies investigated the effect of deferiprone in PKAN, including a recent placebo-controlled double-blind multicenter trial, demonstrating radiological improvement with reduction of iron load in the basal ganglia and a trend to slowing of disease progression. Disease-modifying strategies address the specific metabolic pathways of the affected enzyme. Such tailor-made approaches include provision of an alternative substrate (e.g. fosmetpantotenate or 4’-phosphopantetheine for PKAN) in order to bypass the defective enzyme. A recent randomized controlled trial of fosmetpantotenate, however, did not show any significant benefit of the drug as compared to placebo, leading to early termination of the trials’ extension phase. 4’-phosphopantetheine showed promising results in animal models and a clinical study in patients is currently underway. Another approach is the activation of other enzyme isoforms using small molecules (e.g. PZ-2891 in PKAN). There are also compounds which counteract downstream cellular effects. For example, deuterated polyunsaturated fatty acids (D-PUFA) may reduce mitochondrial lipid peroxidation in PLAN. In infantile neuroaxonal dystrophy (a subtype of PLAN), desipramine may be repurposed as it blocks ceramide accumulation. Gene replacement therapy is still in a preclinical stage.